EFFECTING FACTORS DELIVERED FINANCIAL REPORTING TIME LINES AT MANUFACTURING COMPANY GROUPS LISTED IDX - Sunaryo Sunaryo (Bina Nusantara University, 2012)
The primary objective of this research is to learn the effect among ROA, Leverage, Company Size, and Outsider Ownership with time lines, either partially or simultaneously. Secondary data were collected by purposive sampling of manufacturing company groups listed on IDX and the preceding scientific research journals, using logistic regression to test the hypothesis simultaneously. The results of this research describe that ROA and Leverage do not significant effect to time lines, but company size and outsider ownership have significant effect to time lines. It is recommended that the topic of this research can be continued with merchandising company groups, or service company groups either general or special, like: hotels, insurances, bankings; or, with new independence variables added.